Environmental Challenges for Green Growth and Poverty Reduction : A Country Environmental Analysis for the Lao People’s Democratic Republic - Sánchez-Triana, Ernesto (World Bank, Washington, DC, 2021)
The Environmental Challenges for Green Growth and Poverty Reduction in the Lao People’s Democratic Republic report reveals strong linkages among environmental quality, economic growth, and social wellbeing of the nation’s 7 million inhabitants. This report is a comprehensive presentation prepared after two years of targeted diagnostic research and analysis of issues and conditions within Lao PDR. The analysis was conducted by an international team of World Bank researchers in cooperation with counterparts in lead government agencies in Lao PDR. Information from the Ministry of Health, the Ministry of Natural Resources and Environment, and others, provided an initial basis for the assessments, and this was complemented by other international information. The results can be regarded as a state-of-the-art contribution of information to decision makers in Lao PDR having an interest in achieving sustainable growth consistent with the 2019 National Green Growth Strategy. The report’s scope includes consideration of impacts on key economic sectors and on risk factors influencing the health of the population. The assessments encompassed the economic costs of degradation in the forestry, agriculture, fisheries, mining, and hydropower sectors. The report identifies solid waste management and plastics as an important priority to which the Government of Lao PDR has already pledged its support in regional and global initiatives. Within the context of the Mekong River and its watershed, this report addresses climate-change impacts including increased risks of flooding.